Acceptability and feasibility of healthy diet, physical activity, and hygiene intervention components. (20th October 2021) - Orighoye, O; Maynard, M; Apekey, T
Abstract: : Childhood malnutrition is a major public health concern. We evaluated components and outcome measures for potential interventions promoting a healthy diet, physical activity (PA), and good hygiene among children in Lagos, Nigeria. This mixed-methods study, informed by the Medical Research Council Framework for development of complex interventions, took place in a semi-urban area. Participants in school and community settings were recruited via town criers and community networks. Acceptability and feasibility of 12 intervention sessions (10 school; 2 community) and the Global School-based Student Health Survey (diet, PA, hygiene knowledge/practices questionnaire and body mass index (BMI) measures) were evaluated in qualitative interviews, completion and data quality, respectively. Participants included 130 children aged 8-15yrs; 3 children and their parents took part in qualitative interviews. All 12 sessions were delivered with 100% participation. Session components and delivery were deemed acceptable; however, parents highlighted the timing of the sessions and integration into the school curriculum as potential barriers to sustainability. Researcher capacity and school timing impacted the completion of the survey and measurements (n = 59; 45% response rate). There were no missing questionnaire data. Questionnaire and measurement outcomes were similar across settings except for the proportion of children reporting no handwashing before eating at school (91% school vs 88% community; p = 0.006). This may reflect the inappropriateness of some questionnaire items for non-school attending children. Interventions addressing diet, PA and hygiene may be acceptable and feasible in low resource school and community settings in Nigeria. Increased researcher capacity and adaptation of outcomes measures for non-school attending children may be needed. Key messages: Diet, PA and hygiene interventions may be acceptable and feasible in Nigeria. Researcher capacity and questionnaire adaptation may be needed.